Towards a vision of an Internet of Cultural Things - MAC an AIRCHINNIGH, MICHEAL (My University, 2009)
The Internet of Cultural Things (IoCT) is a phrase we use to denote all those cultural heritage artefacts which have been assigned their own unique IPv6 address and which are equipped with appropriate wireless communication devices. Each such cultural thing, such as a painting, will be able to express its own ontological identity and communicate with its own ?biometric? passport in order to facilitate its exhibition in home museum or abroad. For our own formal backend computing purposes we use a conceptual framework that is an amalgam of top?level ISO standard CIDOC?CRM, realigned with the Sowa?12 framework. Formal encoding is deliberately restricted to OWL2?DL and facilitated by the Protege 4.0 editor from Stanford. The cultural heritage target is the fine arts of/in Bulgaria, a field with which we have been engaged for several
Information Systems & Grid Technologies
PUBLISHED
Sofia, Bulgaria
Keywords: Internet of Things; folksonomy; IPv6; ontology; realignment; smart RFID